Transverse momentum and rapidity dependence of collective flow harmonics of protons and deuterons in Au + Au reactions at 1.23 AGeV. Issue 9 (28th January 2020) - Hillmann, Paula; Steinheimer, Jan; Reichert, Tom; Gaebel, Vincent; Bleicher, Marcus; Sombun, Sukanya; Herold, Christoph; Limphirat, Ayut
Abstract: We explore the rapidity and transverse momentum dependence of collective flow harmonics of deuterons and protons in Au + Au reactions at a beam energy of 1.23 AGeV within the UrQMD approach. These investigations are of direct relevance for the high acceptance di electron spectrometer (HADES) experiment at the GSI Helmholtzzentrum für Schwerionenforschung in Darmstadt, Germany, that has recently presented first data on the flow of light clusters in Au + Au collisions at 1.23 AGeV. To address the deuteron flow, UrQMD has been extended by a phase‐space coalescence approach. We find that this ansatz provides a very good description of the measured deuteron and proton flow data, if a hard equation of state is used for the simulation. The results show a strong impact of cluster formation on the observable collective flow and agree well with the data obtained by the HADES collaboration.